A discrete crack network toolkit for Abaqus for damage and residual strength prediction of laminated composites. (May 2017) - Cui, Xiaodong; Fang, Eugene; Lua, Jim
The main objective of this article is to exploit a phantom paired element based discrete crack network toolkit for predicting the damage progression and residual strength of laminated composites without and with a hole under tension and compression. Both intra-ply matrix cracking and inter-ply delamination are considered under a co-simulation framework in the discrete crack network toolkit. A mesh-independent kinematic description of discrete matrix cracks is accomplished via user-defined phantom paired solid elements to capture the initiation and evolution of fiber orientation dependent matrix cracking. In-ply matrix crack initiation is realized by inserting a crack along the fiber direction when a matrix driven failure criterion is satisfied and a cohesive injection along the matrix crack interface is applied to account for energy dissipation during matrix crack opening. The delamination failure mode is characterized by applying Abaqus' cohesive interaction at ply interfaces. The non-linear shear behavior is introduced by employing a power law based curve-fit model and the fiber failure is described using a continuum damage mechanics based model. Both the blind and recalibrated predictions are performed for specimens of three different layups under the Air Force Tech Scout 1 program. The predicted damage progression and the load displacement curves are compared with the testing results provided by the Air Force Research Laboratory.